Identification of novel candidate genes for susceptibility to tuberculosis by identifying disease-causing mutations in individuals with Primary Immunodeficiency disorders - Schlechter, Nikola (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.